Research progress on the correlation between cataract occurrence and nutrition - Zhang, Yi; Qin, Xiang; Xu, Tianyu; Chu, Fangjing; He, Beihui (Frontiers in Nutrition, 2024)
Cataract is a common eye disease characterized by lens opacity, leading to blurred vision and progressive blindness of the eye. Factors affecting the development of cataracts include nutrition, oxidative stress, micronutrients and inflammatory factors, and also include genetics, toxicity, infrared exposure, hyperuricemia, and mechanical injuries. Among the nutritional factors, a balanced diet, vegetarian diet, dairy products and vegetables are protective against cataracts; high-sodium diet, high intake of carbohydrates and polyunsaturated fatty acids may increase the risk of cataracts; and increased intake of proteins, especially animal proteins, may prevent nuclear cataracts.Intake of antioxidants such as β-carotene, lutein, or zeaxanthin is associated with a reduced risk of cataracts. Minerals such as zinc, selenium, calcium and sodium have also been associated with cataract development. Oxidative stress plays an important role in the development of cataracts and is associated with several antioxidative enzymes and biomarkers such as glutathione (GSH), superoxide dismutase (SOD), malondialdehyde (MDA) and 4-hydroxynonenal (4-HNE). Insulin resistance is also an essential risk factor for cataracts, especially in diabetic patients. In conclusion, understanding these influencing factors helps us to better prevent cataracts. And in this article, we will focus on the important factor of diet and nutrition for a detailed disscussion.